Operative assessment of radioactive contamination of agricultural land for their return to use - Yu. V. Khomutinin; S. E. Levchuk; V. V. Pavlyuchenko (Ядерна фізика та енергетика)
Significant regression dependencies between ambient equivalent dose rate and 137Cs contamination density, as well as between 137Cs and 90Sr contamination densities were obtained. An economically inexpensive approach to estimating the density of soil contamination by 137Cs, 90Sr, and plutonium isotopes with controlled uncertainties has been proposed and tested. The approach allows also the immediate evaluation of the density of radionuclide soil contamination even if there is a contamination gradient within the agricultural land.